Unintended consequences of health policy programs and policies : workshop summary - Young, Wendy Babcock, 1947- (National Academy Press, 2001)
"The Robert Wood Johnson (RWJ) Health Policy Fellowships Program of the Institute of Medicine (IOM) conducted a workshop on August 22, 2000, on the subject of unintended consequences of health policy programs and policies. The purpose of the workshops was to gain a better understanding of why this phenomenon is a frequent and consequential by-product of major health policy programs."--Page 1
Title from caption (viewed November 3, 2001).
"Workshop summary was prepared by ... Wendy B. Young."--Workshop summary p. 1
Keywords: Health planning -- Standards -- United States -- Congresses.; Medical policy -- United States -- Congresses.; Medical care -- United States -- Congresses.; Medical policy.; National Health Programs; Health Policy; United States; Santé publique -- Planification -- Normes -- États-Unis -- Congrès.; Politique sanitaire -- États-Unis -- Congrès.; Assurance-maladie.; Politique sanitaire.; HEALTH & FITNESS -- Health Care Issues.; MEDICAL -- Public Health.; MEDICAL -- Health Policy.; HEALTH & FITNESS -- Diseases -- General.; MEDICAL -- Diseases.; MEDICAL -- Health Care Delivery.; Health planning -- Standards; Medical care; Medical policy; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings.; Actes de congrès.